PROCEDURAL LEGAL STATUS OF THE INVESTIGATOR : POWERS AND FACTORS OF IMPROVEMENT - Khalilov Shоkhrukh Mirzo Boymurod Ogli (International Journal of Business, Law and Political Science, 2024)
Objective: This study examines the legal status and procedural independence of criminal investigators in Uzbekistan, focusing on their crucial role in ensuring fairness and objectivity in criminal investigations. Method: Using a doctrinal research approach, the study analyzes the Criminal Procedure Code of Uzbekistan and scholarly works by K.P. Grigorieva and V.D. Darmaeva. It also reviews case law and practical examples to assess the real-world application of procedural independence, categorizing the findings into themes on investigators' powers, independence, and challenges. Results: The study finds that procedural independence is vital for ensuring fairness in criminal investigations. The legal framework grants investigators broad powers, but challenges such as political pressure, limited resources, and lack of expertise hinder their ability to exercise these powers independently. These challenges underscore the need for stronger protections, resources, and training to support investigators in maintaining objectivity and autonomy. Novelty: This research provides a comprehensive analysis of both the theoretical and practical aspects of procedural independence. It highlights real-world obstacles faced by investigators, emphasizing the importance of adequate legal protections, resources, and professional development to ensure investigators can carry out their duties impartially and effectively, contributing to a just criminal justice system.